Sistem Peramalan Permintaan Darah dengan Metode Simple Moving Average - Wan Mhd Iqbal Muttaqin; William Ramdhan; Wan Mariatul Kifti (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Simple Moving Average (SMA) is a method used to forecast a state of affairs in the next period. This method is applied to determine the number of blood requests in PMI in the Asahan Regency area. Blood stock is an important factor to support activities in this PMI organization by paying attention to the condition of this month /period and predicting the next period. The purpose of this study is to build a blood demand forecasting system with the SMA method. The model used to build this system is a waterfall with stages of analysis, design, implementation and testing. The data we use for this forecasting is the demand for blood from July 2021 to June 2022. Data analysis used the SMA method to determine the rate of prediction errors in this system, while testing this system used a black box. The results of our products are in the form of a web consisting of the login menu, the main menu, the calculation results. The calculation results using the SMA method in our system are appropriate, and can display the number of blood demand stocks in each period. The results of testing the system using black box show that this system is running properly without any errors, and it is working properly. Therefore, the existence of this system can help pmi to determine the number of requests based on blood type.